Force platform fundamentals : an introduction to custom application development in the cloud - McGuire, Chris (Salesforce.com, 2008)
This book introduces you to Force.com, salesforce.com's platform for building and running business applications in the cloud To illustrate the technologies available on the Force Platform, and to show you just how easy it is to create your own business application with the platform, this book walks you through the process of creating a new recruiting application that runs in the cloud. To follow along you won't need to learn any programming languages or hack your way through cryptic configuration documents. Instead, you'll just need to point and click your way through the SalesforceWeb interface, following the easy step by step instructions in the book.